Cholesterol Depletion Suppresses the Translational Diffusion of Class II Major Histocompatibility Complex Proteins in the Plasma Membrane - Vrljic, Marija (The Biophysical Society, 2005)
Glycosylphosphatidylinositol (GPI)-linked and native major histocompatibility complex class II I-E(k) were used as probes to determine the effect of varying cholesterol concentration on the mobility of proteins in the plasma membrane. These proteins were imaged in Chinese hamster ovary cells using single-molecule fluorescence microscopy. Observed diffusion coefficients of both native and GPI-linked I-E(k) proteins were found to depend on cholesterol concentration. As the cholesterol concentration decreases the diffusion coefficients decrease by up to a factor of 7 for native and 5 for GPI-linked I-E(k). At low cholesterol concentrations, after sphingomyelinase treatment, the diffusion coefficients are reduced by up to a factor of 60 for native and 190 for GPI-linked I-E(k). The effect is reversible on cholesterol reintroduction. Diffusion at all studied cholesterol concentrations, for both proteins, appears to be predominantly Brownian for time lags up to 2.5 s when imaged at 10 Hz. A decrease in diffusion coefficients is observed for other membrane proteins and lipid probes, DiIC(12) and DiIC(18). Fluorescence recovery after photobleaching measurements shows that the fraction of immobile lipid probe increases from 8 to ∼40% after cholesterol extraction. These results are consistent with the previous work on cholesterol-phospholipid interactions. That is, cholesterol extraction destroys liquid cholesterol-phospholipid complexes, leaving solid-like high melting phospholipid domains that inhibit the lateral diffusion of membrane components.